2013
DOI: 10.1039/c2dt31624b
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the catalytic properties of rare earth borohydrides for the polymerisation of isoprene

Abstract: Previous results obtained for the cis-polymerisation of isoprene with scandium half-sandwich complex Cp*Sc(BH 4 ) 2 (THF) 1a were extended to its neodymium analog. The X-ray structure of the already reported neodymium monomer compound Cp*Nd(BH 4 ) 2 (THF) 2 1b is presented. Cp*Nd(BH 4 ) 2 (THF) 2 /[CPh 3 ]-[B(C 6 F 5 ) 4 ]/Al( i Bu) 3 catalytic system was found to be very active and stereoselective towards isoprene polymerisation, leading to highly 1,4-cis polyisoprene up to 92%. The effect on isoprene polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 48 publications
4
16
0
Order By: Relevance
“…The M−H bond distances in 8‐La lie between 2.51(6) and 2.83(4) Å and do not differ significantly from the values found for 8‐Nd within the standard deviations. They are also in good agreement with other Nd‐BH 4 complexes reported in literature [17b, 21] . The M−B bond distances of both compounds lie in the range of literature‐reported compounds featuring bridging BH 4 groups, [17g, 18, 19a, 22] but are longer than in species with terminal BH 4 ligands [17b‐e, 21, 23] …”
Section: Resultssupporting
confidence: 88%
“…The M−H bond distances in 8‐La lie between 2.51(6) and 2.83(4) Å and do not differ significantly from the values found for 8‐Nd within the standard deviations. They are also in good agreement with other Nd‐BH 4 complexes reported in literature [17b, 21] . The M−B bond distances of both compounds lie in the range of literature‐reported compounds featuring bridging BH 4 groups, [17g, 18, 19a, 22] but are longer than in species with terminal BH 4 ligands [17b‐e, 21, 23] …”
Section: Resultssupporting
confidence: 88%
“…Alternatively, ionic metathesis from 1 and following the procedure described in previous works [47], afforded a complex (2') that was isolated and stored in the glove box at room temperature. This compound has two THF molecules per Nd atom when freshly isolated [35], but we observed that it displayed a propensity to desolvate and clusterize [50], affecting the THF amounts and solubility properties. As an example, 1 H NMR integration in C 5 D 5 N gave Cp*Nd(BH 4 ) 1.9 (THF) 0.…”
Section: Methodsmentioning
confidence: 79%
“…We disclosed in these recent years a very efficient catalytic system for the polymerization of isoprene, based on the combination of the borohydride Nd(BH 4 ) 3 (THF) 3 as pre-catalyst with a magnesium dialkyl, which afforded a polymer with a high degree of trans-stereoregularity [34,35], along with a good control of macromolecular data. To our knowledge, regarding the trans-selective polymerization of butadiene, Mg dialkyl has been scarcely reported as cocatalyst associated with neodymium versatate [36], alkoxide/aryloxide [37], constrained geometry half-sandwich [38], and more recently with a phosphazen derivative of this lanthanide element [39].…”
Section: Introductionmentioning
confidence: 99%
“…This result is the only example of highly transpolyisoprene synthesized with a scandium catalyst. Coordination of the carbene moiety to the rare-earth center was confirmed by NMR studies on the paramagnetic neodymium pre-catalysts [131].…”
Section: Heterobimetallic Organolanthanide Complexesmentioning
confidence: 91%